Understanding the edge crack phenomenon in ceramic laminates - Ševeček, Oldřich; Kotoul, Michal; Leguillon, Dominique; Martin, Éric; Bermejo, Raul (Gruppo Italiano Frattura, 2015)
In this work, a 2D parametric finite element model has been developed to predict the onset and propagation of an edge crack in ceramic laminates using a coupled stress-energy criterion. This approach states that a crack is originated when both stress and energy criteria are fulfilled simultaneously. Several designs with different residual stresses and a given thickness in the compressive layers have been computed. The results predict the existence of a lower bound, below no edge crack will be observed, and an upper bound, beyond which the onset of an edge crack would lead to the complete fracture of the layer.

In this work, a 2D parametric finite element model has been developed to predict the onset and propagation of an edge crack in ceramic laminates using a coupled stress-energy criterion. This approach states that a crack is originated when both stress and energy criteria are fulfilled simultaneously. Several designs with different residual stresses and a given thickness in the compressive layers have been computed. The results predict the existence of a lower bound, below no edge crack will be observed, and an upper bound, beyond which the onset of an edge crack would lead to the complete fracture of the layer.
Understanding the edge crack phenomenon in ceramic laminates
Keywords: Edge crack; residual stresses; ceramic laminate; FE analysis; coupled criterion.; Edge crack; residual stresses; ceramic laminate; FE analysis; coupled criterion.